(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
First of all, it is necessary to determine that qualimetry is a science of quality. Accordingly, the central concept to be considered will be the quality expressed in a large array of properties and properties. Again, when we consider each subject in its closed evaluation system for the application of qualimetry, the quality is represented by specific indicators. The meaning of qualimetry is to develop the principles of an assessment system that can be applied universally to all objects of research or individual product groups. The object of qualimetry can mean a conditional product in which a certain characteristic (a system of properties and parameters) and a quality control method are applied.